Penatalaksanaa Fisioterapi pada Kondisi Hernia Nucleus Pulposus (HNP) pada L5-S1 di RSUD Salatiga - Cahyati, Yunisa Ida, Dwi Rosella Komala Sari S.St.Ft. M.Fis (2015)
Background:(Hernia Nucleus Pulposus) HNP is condition that protusion can occurs on the discus intervertebralis caused by injury or the wrong mechanic load in a long time. Beside, the main factor of HNP is a degenerative condition. When elasticity of annulus fibrosus decrease, it may bulge or rupture. Gluteal and unilateral leg pain are the common condition perceived by the HNP Patient, depend on the nerve root compression. The other conditions that can happen on a HNP patient are the decrease in Range Of Motion (ROM), loss of leg muscle strength, and spasm in the related location. Purposes: to know how physiotherapy can reduce the pain, increase the muscle strength, and improve the functional activities in HNP L5-S1 case using the Transcutaneus Electrical Nerve Stimulation (TENS), Activation Deep Muscle Exercise, and Isotonic Resistive Exercise. Result:After six time of therapy, the results for the assessment were pain at rest T1: 2 and T6: 1, tenderness T1: 4 and T6: 2, Pain at activity T1: 5 and T6: 2, an increase of the muscle strength in the hip extensor T1: 3 and T6: 4, knee extensor T1: 3 and T6: 4. Ankle extensor T1: 3 and T6: 4, decrease Incapability Self Care T1: 2 and T6: 1, Lifting T1: 2 and T6: 1, Walking T1: 2 and T6: 1, Sitting T1: 2 and T6: 1, Standing T1: 3 and T6: 2, Travelling T1: 5 and T6: 2. In a matter of social life, there was no change to be found, it was T1: 3 and T6: 3 and for the pain intensity and sleep there was no disturbance. Conclution:Transcutaneus Electrical Nerve Stimulation (TENS) can rduce the pain of HNP on L5-S1. Activation Deep Muscle Exercise can resuce pain due to the instability of lumbal spine. TENS and Activation Deep Muscle Exercise on the HNP L5-S1 case can improve functional activities, and Isotonic Resistive Execise on this case can increase the muscle strength. Key Words: Hernia Nucleus Pulposus (HNP), Transcutaneus Electrical Nerve Stimulation (TENS), Activation Deep Muscle Exercise, and Isotonic Resistive Exercise.